From Separation to Integration: Identity Development of Korean Adult Players in Online Game World - Doh, Young Yim; Whang, Sang-Min Leo (Games and Culture, 2014)
This research examined the identity development of Korean adult players in the online game world. Q methodology was used to investigate the subjectivity of self-development in Mabinogi (Massive Multiplayer Online Role-Playing Game). Thirty-seven adult players sorted 57 behavior statements to reflect the changes in their behaviors from past to present. Three types of self-development were found: achievement-oriented development, control-oriented development, and relational development. The behavior patterns of these three types were compared to identify similarities and differences among them in terms of psychological meanings and values in the online game life. The results illustrate that the online game world can be defined as a new behavioral setting, made possible by digital technology, in which individuals are able to experience three different paths of identity development.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé